2016
DOI: 10.1039/c6ra10902k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristics of graphene oxide nanosheets on cement

Abstract: aThe graphene oxide (GO) nanosheets modified cement tremendously improved their mechanical properties but decreased the fluidity. The adsorption characteristics between GO and cement plays a pivotal role for the influence on fluidity. In this paper, the adsorption characteristics of graphene oxide nanosheets on cement were investigated by scanning electron microscope (SEM), total organic carbon (TOC), Fourier transform infrared spectra (FTIR) and XPS. The results show that GO nanosheets have a strong adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…At the same time, the cloudy GO flocculation settled down with the increasing CH dosage. The results were in good agreement with the conclusions obtained in other researches (5,19,20).…”
Section: Flocculation Of Go In Ch Solutionsupporting
confidence: 92%
“…At the same time, the cloudy GO flocculation settled down with the increasing CH dosage. The results were in good agreement with the conclusions obtained in other researches (5,19,20).…”
Section: Flocculation Of Go In Ch Solutionsupporting
confidence: 92%
“…Previous reports suggested that GO adsorbs onto the surface of PC particles while mixing the paste [33], as also discussed in the introduction. However, based on the results shown in Sections 3.1-3.3, if GO interacts with the surface of hydrating particles, one should clearly expect a delay in hydration.…”
Section: Dominant Role Of Go In Pc Pastementioning
confidence: 76%
“…GO layers become even more negatively charged in alkaline solutions, as more carboxyl sites are deprotonated [32]. Wang et al [33] suggested that carboxylated GO adsorbs onto the surface of PC particles in the paste. This mechanism is plausible because PC grains are known to possess a positive electrostatic charge in water [34], so in principle, GO layers could be attracted to PC surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The formed aggregation in this way can reach the micron scale and thus should not be neglected. 45 Silica fume is then adopted to mechanically and chemically separate GO nanosheets from calcium ions by means of reacting with Ca(OH) 2 . Meanwhile, calcium silicate hydrate, the main product of cementitious materials, has silicate hydroxyl and calcium hydroxyl groups near the surface, which will form stable H-bonds connection with GO.…”
Section: Dispersion Of Gnp and Go In Cementitious Materialsmentioning
confidence: 99%